The particle image velocimetry method in the study of the dynamics of phase transitions induced by high pressure in triolein and oleic acid - Tefelski, D.B.; Kulisiewicz, Leszek; Wierschem, Andreas; Delgado, Antonio; Rostocki, Aleksander; Siegoczyński, Ryszard Maciej (High Pressure Research, 2011)
Particle image velocimetry (PIV) is an optical measurement method capable of providing visualisation of velocity field of particle flow in fluids. After analysis of data acquired in the form of an image sequence, it is possible to retrieve information about flow parameters as mean values of velocity, vorticity, shear and normal strain. This paper presents the results of high pressure experiments using this method applied to triolein and oleic acid samples in their phase transition region. A high pressure optical chamber, He-Ne laser and light-sheet optics together with a digital camera and image acquisition computer allow us to study the motion of particles in high pressure conditions. The set-up was similar to that presented in Ozmutlu et al. [Momentum and energy transfer during phase change of water under high hydrostatic pressure, Innov. Food Sci. Emerg. Technol. 7(3) (2006), pp. 161-168] and Kulisiewicz et al. [Visualization of pressure-shift freezing and thawing of concentrated aqueous sucrose solutions, High Press. Res. 27(2) (2007), pp. 291-297]. The analysis of phase transition dynamics in triolein and oleic acid is an extension to the work presented in Tefelski et al. [The investigation of the dynamics of the phase transformation in triolein and oleic acid under pressure, J. Phys.: Conf. Ser. 121(142004) (2008), pp. 1-6]. Oleic acid is a monounsaturated fatty acid and has a bent rod shape. Triolein is a triglyceride and has a chair-like shape. It is the base particle of many vegetable oils, especially olive oil. Triolein consists of three chains of oleic acid bound by a glycerol part. Information obtained by the study of phase transitions dynamics is important for food science and food technology processes which involve high pressure treatment. The PIV method shows differences in the solidification process of both substances in time, the existence of inhomogeneities (layers of different densities in the observed flow) and allows us to calculate the parameters of flow using the PIVview2C software from PIVTEC GmbH. © 2011 Taylor & Francis.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.thepar
Keywords: oleic acid; phase transition; PIV; triolein